Measuring Cognitive Efficiency of Novel Speedometer Displays. (September 2016) - Yang, Shiyan; Ferris, Thomas K.
Cognitive efficiency has been defined as the ratio of display informativeness to mental workload required for processing information. In the study, we used Cognitive Efficiency (CE) metric to measure the efficiency of novel speedometer displays which were previously used to aid multitask performance in driving. The study also investigated whether encoding information into 'beat pattern', a redundant dimension, improves the cognitive efficiency of the displays. The level of cognitive efficiency was found to be similar among the ambient-visual, auditory, and tactile speedometer displays and it increased largely when information was encoded into a redundant beat pattern of the auditory display. In addition, the cognitive efficiency of novel speedometer display was sensitive to contextual factors such as wind effects. These findings enlarge our understanding of multifactor constructs of cognitive efficiency, which are expected to be more predictive of multitask performance than the measure of each of its constituent components.